Unusual localized gingival redness: a case report - Kumar, Swati; Sujir, Nanditha; Saha, Anwesha; Ahmed, Junaid; Bhushan, Prem (Frontiers in Oral Health, 2023)
Inflammation of the gingiva is one of the most common and routine findings in a dental practice. These routine appearances of an inflammatory gingiva can show peculiarity when it is associated with an underlying systemic condition or due to reactive, benign, or malignant pathologies. This case highlights minute clinical signs of the gingiva that deviate from the routine presentation and warrants further investigations. A 63-year-old women presented with a chief complaint of severe pain in relation to lower front teeth region for one month. Intraoral examination revealed a gingival lesion on the labial aspect of 41, 42, 43 with an intraoral periapical radiograph that showed mild bone loss. The lesion persisted despite oral prophylaxis and a biopsy was advised. The final diagnosis was Gingival squamous cell carcinoma (GSCC) Stage 1. It is important to note that the nondescript presentation of GSCC in early stages often mimics benign traumatic or inflammatory lesions of gingiva. Peculiar clinical features of GSCC of note include, the lack of traditional risk factors associated, localized red or ulcerative lesions with increased bleeding tendencies that do not respond to routine periodontal treatment within 2 weeks.